Simultaneous synthesis and synergetic stabilization of Zr-doped and Li6Zr2O7-coated Ni-rich layered cathode for advanced lithium ion batteries. (20th December 2020) - Yang, Huiping; Li, Lingjun; Liu, Chaoyang; Chen, Jie; Xia, Lingfeng; Liu, Zengsheng; Chen, Jiaxin; Chen, Zhaoyong; Duan, Junfei
Abstract: Ni-rich cathode materials, one of the most promising cathodes for high-energy lithium-ion batteries, are still suffered from interfacial instability and bulk degradation. Herein, Zr-doped and Li6 Zr2 O7 -coated LiNi0.8 Co0.1 Mn0.1 O2 cathode, and Zr-doped Li6 Zr2 O7 –LiNi0.8 Co0.1 Mn0.1 O2 composite are successfully prepared via a smart one-step calcination process. The attained dual-modified architecture allows the optimized sample exhibiting enhanced rate performance while maintaining long-term stability at room temperature (82.13% after 200 cycles at 1 C rate) and even at elevated temperature. Further studies reveal that the delayed temperature-driven phase transition and the suppressed interfacial degradation can be addressed with the synergetic effects provided by the Zr-doping and Li6 Zr2 O7 -coating. The Zr doping could improve bulk stability by reducing cation disorder. The conductive Li6 Zr2 O7 surface coating enhances the interfacial stability of the cathode materials while improving the electrochemical kinetics. This smart modification strategy renders Zr modification a viable modification method to enhance the electrochemical performance and structural properties of Ni-rich cathode materials. Abstract : Lithium ion batteries have been powering our daily life from portable electronic devices to electric vehicles [1 –3] . The lack of cathode materials with high reversible capacities and high thermal stability is still a restriction for the development of high-energy LIBs. Among the adopting options as an alternative to traditional LiCoO2 material, the layered Ni-rich ternary materials LiNi x Co y Mn1- x - y O2 ( x ≥0.5) are considered as promising candidates because of their increased energy densities and reduced cost [4 –7] . Specially, LiNi0.8 Co0.1 Mn0.1 O2 (NCM) has been attracting much attention by virtue of high specific capacity of delivering more than 200 mAhg −1 of discharge capacity [8 –11] . Graphical abstract: Image, graphical abstract